1994
DOI: 10.1111/j.1365-2923.1994.tb02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Does learning emergency medicine equip medical students for ward emergencies?

Abstract: The aim of this study was to assess the competence of senior medical students in recognizing and managing life-threatening ward emergencies and to compare the competence of a group that had received emergency medicine teaching with one that had not. This was achieved by asking 60 final year medical students to complete a structured written clinical examination designed to test these skills. Comparisons were made between the group that had received emergency medicine teaching (the 'taught' group) and that which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
2
10
0
1
Order By: Relevance
“…In contrast, insignificant relation between the difference of the knowledge scores and participants' age, internship duration, and passing major rotations in clinical blocks, suggests that emergency medicine education teaches many clinical knowledge and skills that have not been achieved in the other curricula before. Several investigations corroborate these findings [13][14][15].…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, insignificant relation between the difference of the knowledge scores and participants' age, internship duration, and passing major rotations in clinical blocks, suggests that emergency medicine education teaches many clinical knowledge and skills that have not been achieved in the other curricula before. Several investigations corroborate these findings [13][14][15].…”
Section: Discussionsupporting
confidence: 57%
“…They found that students who had taken emergency medicine got better scores than those who had not (P < 0.001). Therefore, they suggested that studying emergency medicine could improve the skills of senior medical students in critical situations in wards (7). These studies were all based on the effective learning and training self-stemmed personnel and practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies had suggested that formal instruction in emergency skills is important, since it resulted in improved doctors’ procedural competence and reduced the rate of fatal errors [1,2]. Unfortunately, many residents reported a lack of confidence in performing the invasive procedures to their patients [3].…”
Section: Introductionmentioning
confidence: 99%